Strategi Diskusi, Audiovisual dan Praktik yang Dilakukan Guru dalam Mengajar Siswa Kesulitan Belajar di Kelas IV SDN 141 Pekanbaru - Afifah Hannum; Zaka Hadikusuma Ramadan (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The aim of this research is to describe the methods used by teachers at SDN 141 Pekanbaru grade 4 in teaching students who experience learning failure. This research uses the same methodology as previous research, namely qualitative research with a case study approach. Teachers and students were used as the main data sources in this research. In this research, documentation, interviews and observation are the methods used to collect data. There are three steps in data analysis techniques: data reduction, data presentation, and data verification. Research findings show that a number of students experience difficulties in reading, writing and arithmetic. These problems represent specific learning challenges. To overcome this problem, educators must choose acceptable and successful strategies, approaches, methods and teaching and learning procedures that they can use as a guide in implementing learning activities.